البعد التاريخي في الرواية الجزائرية المعاصرة -رواية سفر القضاة لأحمد زغب- أنموذجا - بلال, عزوز; فاتنة, فتاتي (جامعة الوادي - University of Eloued, 2023)
يعتبر التاريخ من أهم مصادر الرواية المغاربية التي حاولت الاستنجاد والاستفادة منه، لما يحمله هذا التاريخ من حمولة معنوية وفكرية، وحركية ثقافية، حيث ركزت الرواية الجزائرية على وجه الخصوص على استدعاء التاريخ وصهره في بناءها السردي والحكائي. وفي هذه الورقة البحثية اخترنا نموذج معاصر من الرواية الجزائرية (رواية سفر القضاة لأحمد زغب)، التي استلهمت من التاريخ الكثير من الأحداث والشخصيات المحلية، لكن الهدف المرجو من هذا البحث هو كشف علاقة الرواية بالتاريخ، والبحث في لازمة التاريخ في العمل الروائي الجزائري المعاصر. لأن اشتغال رواية ما على التاريخ يقتضي الإلمام بالأحداث التاريخية من طرف الروائي وخلق نوع من التوازن والتناغم بين ما هو جمالي أدبي وما هو تاريخي موضوعي، وهذا ما سنكتشفه عند الروائي والأكاديمي أحمد زغب من خلال رواية سفر القضاة. History is one of the most important sources of the Maghreb novel that tried to find and take advantage of it, for what this history cares of a Moral and intellectual load, and Cultural mobility, when the The Algerian narrative focused in particular on invoking history, and fuse it to its Narrative and anecdotal construction. So, in this research paper we choosed a modern model of Algerian novel (Ahmad Zaghab’s Sifr Al-Qudhat novel), that inspired from history a lot of events and local figures, but the Objective of this research is to reveal the relationship between novel and history, and to explore the history requisite to the Algerian modern novelist work. Because to get interested to a history novel requires the novelist to be aware of the historic events and to create a type of balance and harmony between what is literary aesthetic and what is Objective Historical, and That's what we'll discover at the novelist and the academic Ahmad Zaghab through his novel “Sifr Al-Qudat”(the book of judges).
مقال
Keywords: تاريخ؛ رواية؛ السرد؛ سفر القضاة؛ أحمد زغب.; history ; novel; narrative; Sifr Al-Qudhat; Ahmad Zaghab.